(untitled) (Research, Society and Development, 2021)
Pneumoperitoneum is characterized by the presence of abdominal cavity gas. Thus, this is used as a tool to create a space in the abdominal cavity for video laparoscopic surgical procedures. However, insufflation of abdominal cavity is capable of causing damage induced by tissue ischemia and reperfusion, which is caused by hypoxia and an imbalance between free radical production and antioxidant defense system capacity. The objective of this study was to bibliographic review the negative effects of exposing healthy animals to different pneumoperitoneum settings by assessing oxidative stress and testicular histopathology, identifying intra-abdominal pressures that did not result in testicular alteration. A systematic search was carried out in three databases using the following terms: pneumoperitoneum AND testi* or gonad. The survey conducted in the databases yielded 2209 scientific articles. After applying inclusion and exclusion criteria, six papers were selected. All the articles selected addressed the effects of pneumoperitoneum on testicular structure and used at least one scoring system to perform histopathological evaluation of the testis. Three studies verified the occurrence of changes in oxidative stress. According to this literature review, pneumoperitoneum used at intra-abdominal pressures equal to, or greater than, 9 mmHg caused testicular histological damage. According to the biomarkers used in studies, pressures greater than 10 mmHg were sufficient to cause testicular oxidative stress.